Biorecycling of Organic Waste as a Universal Ecoclimatic Project and Increasing the Resource Capacity of Cultural and Natural Ecosystems - Bukharina, Irina Leonidovna; Didmanidze, Otari Nazirovich; Pashkova, Anna Sergeevna; Kovalchuk, Andrey Gavrilovich; Larionov, Maxim Viktorovich; Islamova, Nadezhda Alexandrovna; Belelya, Alexandra Sergeevna; Zaitseva, Tatyana Alexandrovna; Butenko, Sergey Alekseevich (Journal of Ecohumanism, 2024)
The problem of organic waste generation has long grown into a global environmental problem. There are different methods for recycling organic waste of various origins and morphological states. But the vast majority of the organic component of the total mass of waste generated in the world is not processed effectively. In 2022 together with industrial partners, the research and production site (RPS) was created for the development and testing of technologies for recycling organic waste using insects, and (hereinafter referred to as the RPS). During this period technical specifications were developed and registered for the production of two products of biorecycling of organic waste by Hermetia illucens larvae (feed for unproductive animals – dogs, cats, chickens, geese, ducks, pigs) and vermicompost enriched with beneficial microflora. The scientific group of the RPS, in collaboration with representatives of universities and research centers from different regions of Russia, with the support of the Sibur company, developed the ecoclimate project to create five enterprises in the Western Cis-Urals for the biorecycling of organic waste. Using five organic waste landfills as an example, it is shown that the environmental and economic efficiency will be 180 thousand tons of CO2-eq./year of carbon units. The level of biorecycling of organic agricultural and other waste is 120 thousand tons/year and more. Thus, it is possible to eliminate the deficit in the market for secondary raw materials, vermicompost and feed additives. This is aimed at achieving ecologically and climate-optimized organic farming. The results and material of our work can be used in handling organic waste from crop and livestock production, from the agro-feed and food industries, from public utilities. The work can be a scientific and methodological basis for biorecycling of organic waste from urban economic facilities and other areas of public production. This is the example of modern environmental culture and ecologized self-awareness of nature users.